The discipline of enterprise engineering. (1st January 2013) - Dietz, Jan L.G.; Hoogervorst, Jan A.P.; Albani, Antonia; Aveiro, David; Babkin, Eduard; Barjis, Joseph; Caetano, Artur; Huysmans, Philip; Iijima, Junichi; van Kervel, Steven; Mulder, Hans; Op 't Land, Martin; et al.
A century ago, Taylor published a landmark in the organisational sciences: his Principles of Scientific Management . Many researchers have elaborated on Taylor's principles, or have been influenced otherwise. The authors of the current paper evaluate a century of enterprise development, and conclude that a paradigm shift is needed for dealing adequately with the challenges that modern enterprises face. Three generic goals are identified. The first one, intellectual manageability, is the basis for mastering complexity; current approaches fall short in assisting professionals to master the complexity of enterprises and enterprise changes. The second goal, organisational concinnity, is conditional for making strategic initiatives operational; current approaches do not, or inadequately, address this objective. The third goal, social devotion, is the basis for achieving employee empowerment as well as knowledgeable management and governance; modern employees are highly educated knowledge workers; yet, the mindset of managers has not evolved accordingly. The emerging discipline of Enterprise Engineering, as conceived by the authors, is considered to be a suitable vehicle for achieving these goals. It does so by providing new, powerful theories and effective methodologies. A theoretical framework is presented for positioning the theories, goals, and fundamentals of enterprise engineering in four classes: philosophical, ontological, ideological and technological.